EFL Learners’ Ability in Reading Scientific Text in TOEFL - Maspufah Maspufah (Universitas Pahlawan Tuanku Tambusai, 2022)
TOEFL as one type of test is commonly used to measure learners’ English proficiency. TOEFL consist of reading comprehension, listening, structure and written expression. However learners got difficulties to do reading section, especially in reading scientific text due to its condensed information and different terms with general English. The aim of this research was to find out EFL learners’ ability in reading scientific text of TOEFL. Descriptive quantitative method was applied to the research. The subject of the research was 8 learners of the fourth semester of 2019/2020 academic year STIBA Persada Bunda Pekanbaru. The instrument used to collect the data was reading test in the form of multiple choice tests. The data were analysed by using descriptive statistics to find the level of learners’ ability in reading scientific text in TOEFL. From the finding, it was found EFL learners individual score average was 79. The highest score was in previewing and the lowest score was in making inferences and identifying exception. In brief, it could be concluded that EFL learners’ ability in reading scientific text were in intermediate category.